Counter Radicalization and the Role of Local Governance in Cilacap - Kusuma, Ayusia Sabhita; Bintarsari, Nuriyeni (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2024)
This research aims to find out what roles and cooperation are carried out by the local government in counter-radicalism efforts in Cilacap Regency. So far, there have been numerous studies on the threat of radicalism and terrorism in Indonesia. However, few examine the threat of radicalism, terrorism, and counter-radicalization strategies at the local level. Furthermore, Indonesia lacks many regional or local regulations targeting counter-radicalization strategies. Cilacap Regency is one of the regencies that is prone to radicalism and terrorism. Therefore, prevention and counter-radicalization against the threat of terrorism in Cilacap are needed, especially through cooperation between local government actors. This research uses qualitative research methods and data collection methods in the form of in-depth interviews and focus group discussions (FGDs) involving several elements of government and community groups. Using the concept of multisectoral governance, the result of this study is that multisectoral cooperation between various elements has been realized in counter-radicalization efforts in Cilacap Regency. However, some challenges remain, including the absence of a Regency Regulation (Peraturan Bupati) for handling terrorism in Cilacap.